The night of the hunter [videorecording (DVD)] - Laughton, Charles, 1899-1962; Mitchum, Robert; Winters, Shelley; Gish, Lillian, 1893-1993; Gleason, James, 1886-1959; Varden, Evelyn, 1893-1958; Grubb, Davis, 1919-1980 (Criterion collection, 2010)
A self-styled preacher marries and murders the widow of an executed convict with whom he once shared a cell. He then terrorizes her two young children to force them to tell him the whereabouts of the $10,000 he knows their father hid before his imprisonment.